T‐cell infiltration, contribution and regulation in the central nervous system post‐traumatic injury. (29th June 2021) - Xu, Lvwan; Ye, Xin; Wang, Qingyi; Xu, Bihan; Zhong, Jinjie; Chen, Ying‐ying; Wang, Lin‐lin
Abstract: T cells participate in the repair process and immune response in the CNS post‐traumatic injury and play both a beneficial and harmful role. Together with nerve cells and other immune cells, they form a microenvironment in the CNS post‐traumatic injury. The repair of traumatic CNS injury is a long‐term process. T cells contribute to the repair of the injury site to influence the recovery. Recently, with the advance of new techniques, such as mass spectrometry‐based flow cytometry, modern live‐cell imaging, etc, research focusing on T cells is becoming one of the valuable directions for the future therapy of traumatic CNS injury. In this review, we summarized the infiltration, contribution and regulation of T cells in post‐traumatic injury, discussed the clinical significance and predicted the future research direction. Abstract : The dynamic infiltration and the contribution of T cells in the CNS post‐traumatic injury. CD8 + T cells mediate neuronal apoptosis. Th1 cells and Th17 cells play pro‐inflammatory roles, while Th2 cells and Treg cells play anti‐inflammatory roles.